The plastics handbook. - Lefteri, Chris, ....- (Mies : Rotovision, 2008)
Explores traditional and innovative applications of different plastics From plastics with the strength and durability of metal, to mass-produced skins, sensuous plastics, and rental DVDs that expire 48 hours after you've opened the packaging, The Plastics Handbook offers a fascinating insight into the most innovative and unusual plastics for designers and manufacturers throughout the world. This book gets under the skin of products and materials to reveal the hidden qualities of plastics, exploring the materials that surround us today, and those that will surround us tomorrow, together with their practical applications. The Plastics Handbook is your essential guide to who is making what, from contemporary designer materials to the products of the future, featuring facts and applications for hundreds of new plastic products and materials. The book also has an extensive resources section, including a glossary, a guide to different types of plastics, diagrams of standard manufacturing processes, plus useful website addresses.
Keywords: Industrieel ontwerpen; Plastics